Sensors Innovations for Smart Lithium-Based Batteries: Advancements, Opportunities, and Potential Challenges - Moradian, Jamile Mohammadi; Ali, Amjad; Yan, Xuehua; Pei, Gang; Zhang, Shu; Naveed, Ahmad; Shehzad, Khurram; Shahnavaz, Zohreh; Ahmad, Farooq; Yousaf, Balal (Nano-Micro Letters, 2025)
Lithium-based batteries (LiBs) are integral components in operating electric vehicles to renewable energy systems and portable electronic devices, thanks to their unparalleled energy density, minimal self-discharge rates, and favorable cycle life. However, the inherent safety risks and performance degradation of LiB over time impose continuous monitoring facilitated by sophisticated battery management systems (BMS). This review comprehensively analyzes the current state of sensor technologies for smart LiBs, focusing on their advancements, opportunities, and potential challenges. Sensors are classified into two primary groups based on their application: safety monitoring and performance optimization. Safety monitoring sensors, including temperature, pressure, strain, gas, acoustic, and magnetic sensors, focus on detecting conditions that could lead to hazardous situations. Performance optimization sensors, such as optical-based and electrochemical-based, monitor factors such as state of charge and state of health, emphasizing operational efficiency and lifespan. The review also highlights the importance of integrating these sensors with advanced algorithms and control approaches to optimize charging and discharge cycles. Potential advancements driven by nanotechnology, wireless sensor networks, miniaturization, and machine learning algorithms are also discussed. However, challenges related to sensor miniaturization, power consumption, cost efficiency, and compatibility with existing BMS need to be addressed to fully realize the potential of LiB sensor technologies. This comprehensive review provides valuable insights into the current landscape and future directions of sensor innovations in smart LiBs, guiding further research and development efforts to enhance battery performance, reliability, and safety. Highlights: 1 Sensors for smart Lithium-based batteries (LiBs) are classified based on their application into safety monitoring (i.e., temperature, pressure, and strain) to detect hazardous conditions and performance optimization (i.e., optical and electrochemical sensors) for monitoring factors such as state of charge and state of health. 2 The potential for innovation in LiB sensor technology is driven by advancements in nanotechnology, miniaturization, machine learning algorithms, and wireless sensor networks, all of which contribute to enhanced sensor performance. 3 Key challenges faced in developing LiB sensors include miniaturization, power consumption, cost efficiency and scalability, and compatibility with existing battery management systems.